2014
DOI: 10.11646/zootaxa.3835.2.9
|View full text |Cite
|
Sign up to set email alerts
|

On the Reclassification of the Terrapene (Testudines: Emydidae): A Response to Fritz & Havaš

Abstract: The American box turtles (Terrapene spp.) consist of four historically recognized species based primarily on morphological data (Minx 1996): Terrapene carolina (Linnaeus), T. ornata (Agassiz), T. nelsoni (Stejneger), and T. coahuila (Schmidt & Owens). Each of these species is polytypic except for T. coahuila. Recently, the Placyk lab re-assessed the classification of Terrapene using molecular phylogenetic data, and suggested elevating a clade consisting of T. carolina triunguis (Agassiz), T. c. mexicana (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Our conclusion is supported by the alternate phylogeny reported by Spinks et al (2009), a study not mentioned by Martin et al (2013Martin et al ( , 2014. Using sequences of the cyt b gene and seven nuclear loci, Spinks et al (2009) found T. c. bauri clustering with T. c. triunguis ( Fig.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…Our conclusion is supported by the alternate phylogeny reported by Spinks et al (2009), a study not mentioned by Martin et al (2013Martin et al ( , 2014. Using sequences of the cyt b gene and seven nuclear loci, Spinks et al (2009) found T. c. bauri clustering with T. c. triunguis ( Fig.…”
supporting
confidence: 85%
“…Like Martin et al (2013), Spinks et al (2009) found T. carolina to be paraphyletic with respect to T. coahuila. However, for the rapidly evolving D-loop Butler et al (2011) found T. carolina not to be paraphyletic with respect to T. coahuila.…”
mentioning
confidence: 90%
See 3 more Smart Citations